Community-based adaptation to climate change in small island developing states: an analysis of the role of social capital. (14th September 2019) - Hagedoorn, L.C.; Brander, L.M.; van Beukering, P.J.H.; Dijkstra, H.M.; Franco, C.; Hughes, L.; Gilders, I.; Segal, B.
ABSTRACT: In the context of climate change, small island developing states (SIDS) need to engage in adaptation efforts. Due to the rural, remote and specific institutional characteristics of SIDS, these efforts are commonly implemented at the community level. Therefore, the adaptive capacity of the community is an essential attribute of the adaptation process. With a focus on the role of social capital, this paper provides a quantitative analysis of determinants of household intention to participate in community adaptation projects, using data from a household survey and discrete choice experiment conducted in a coastal community in the Federated States of Micronesia. The results reveal that expectation of high climate change risks and strong sense of social capital enhance adaptive capacity. Participation in community activities and perception of threats to the social group in question are important components of social capital in determining adaptive capacity. Household size, income diversification, and very high resource dependency are negatively related to the household's intention to contribute to community adaptation and therefore adaptive capacity. These results provide crucial insights for the design and implementation of community adaptation projects in SIDS.